2017
DOI: 10.1038/s41598-017-11282-1
|View full text |Cite
|
Sign up to set email alerts
|

Testing Gait with Ankle-Foot Orthoses in Children with Cerebral Palsy by Using Functional Mixed-Effects Analysis of Variance

Abstract: Existing statistical methods extract insufficient information from 3-dimensional gait data, rendering clinical interpretation of impaired movement patterns sub-optimal. We propose an alternative approach based on functional data analysis that may be worthy of exploration. We apply this to gait data analysis using repeated-measurements data from children with cerebral palsy who had been prescribed fixed ankle-foot orthoses as an example. We analyze entire gait curves by means of a new functional F test with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Furthermore, functional curve analyses have advantages over alternatives such as multiple pointwise tests along the curves, which require corrections of P values (Bonferroni etc) to more conservative levels. (Pataky et al, 2013;Roislien et al, 2009;Thoresen and Gjessing, 2012;Zhang et al, 2017) Limitations exist in testing effects of relevant continuous covariates such as speed when the dependent variable is a function. (Roislien et al, 2009) In comparison, the linear mixed model analysis with peak FZ 1 and FZ 2 dependent variables enables evaluation of both categorical and continuous covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, functional curve analyses have advantages over alternatives such as multiple pointwise tests along the curves, which require corrections of P values (Bonferroni etc) to more conservative levels. (Pataky et al, 2013;Roislien et al, 2009;Thoresen and Gjessing, 2012;Zhang et al, 2017) Limitations exist in testing effects of relevant continuous covariates such as speed when the dependent variable is a function. (Roislien et al, 2009) In comparison, the linear mixed model analysis with peak FZ 1 and FZ 2 dependent variables enables evaluation of both categorical and continuous covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming gait curves to continuous functions of time has previously demonstrated benefits over more traditional methods to assess kinematic gait curves. (Roislien et al, 2009) More recently, Zhang et al proposed a functional mixed-effects analysis to study kinematic gait curves in children with CP walking with and without AFOs (Zhang et al, 2017). Such approaches would enable comparisons of vGRF curves with greater reliability, (White et al, 1999) before and after intervention, over the entire and parts of the stance phase, and corresponding to the periods where FZ 1 and FZ 2 occur.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [33] 2017 The beneficial outcomes of orthoses are observed more in the sagittal plane than in coronal and horizontal planes.…”
Section: Papavasiliou Et Al [30] 2013mentioning
confidence: 99%
“…Orthoses restore the power of muscles and require less energy to walk, and they also provide adequate support to the limbs to walk properly on the ground [ 32 ]. The beneficial outcomes of orthoses are observed more in the sagittal plane than in coronal and horizontal planes [ 33 ]. As the knee joint is the main joint involved in the movement of limbs, orthoses are the most effective assisted devices used to increase the range of movements and support patients.…”
Section: Reviewmentioning
confidence: 99%